STOPAN Policy as an Effort to Reduce Child Marriage: A Review of Public Policy Based on Maqashid Syariah - Azhari, Ahmad; Sugianto, Sugianto; Djumhur, Adang; Setyawan, Edy; Syaefullah, Syaefullah (Jurnal Adabiyah, 2025)
Child marriage is still a crucial social problem in Indonesia, one of the provinces with the highest rate of underage marriage is West Java Province nationally. This practice not only violates children's rights, but also has an impact on their future, some drop out of school, ongoing poverty, and domestic violence. To respond to this problem, the West Java Provincial Government through the Women's Empowerment, Child Protection, and Family Planning Service (DP3AKB) initiated the Stop Child Marriage (STOPAN) program. This program involves cross-sector collaboration—government, academics, business, media, and communities—with a comprehensive and participatory approach to reduce the number of child marriages. This study aims to analyze the implementation of the STOPAN program in reducing the number of child marriages and evaluate its effectiveness from the perspective of Maqashid Syariah. The approach used is qualitative-descriptive with a case study method. The results of this study indicate that STOPAN is quite effective partially. The number of marriage dispensations decreased from 6,794 cases (2021) to 3,631 cases (2024), and the proportion of women aged 20–24 who married before 18 also decreased from 10.09% to 5.78%. However, the practice of unregistered marriage is still often carried out by some communities. From the perspective of Maqashid Syariah, STOPAN contributes to the protection of religion, soul, mind, descendants, and property, although it is not yet fully optimal. This study recommends strengthening the community-based approach and the integration of local religious and cultural values ​​in the implementation of STOPAN. ملخص لا يزال زواج الأطفال قضية اجتماعية بالغة الأهمية في إندونيسيا. تُعدّ مقاطعة جاوة الغربية من بين المقاطعات التي تشهد أعلى معدلات زواج القاصرات على المستوى الوطني. لا تنتهك هذه الممارسة حقوق الأطفال فحسب، بل تؤثر أيضًا على مستقبلهم، مما يؤدي إلى التسرب من المدارس، واستمرار الفقر، والعنف الأسري. ولمعالجة هذه القضية، أطلقت حكومة مقاطعة جاوة الغربية، من خلال وكالة تمكين المرأة وحماية الطفل وتنظيم الأسرة (DP3AKB)، برنامج "وقف زواج الأطفال" (STOPAN). يتضمن هذا البرنامج تعاونًا بين القطاعات المختلفة - الحكومة، والأوساط الأكاديمية، وعالم الأعمال، ووسائل الإعلام، والمجتمعات المحلية - مع اتباع نهج شامل وتشاركي للحد من معدلات زواج الأطفال. تهدف هذه الدراسة إلى تحليل تطبيق برنامج STOPAN في الحد من معدلات زواج الأطفال، وتقييم فعاليته من منظور مقاصد الشريعة الإسلامية. وقد استخدم المنهج الوصفي النوعي مع دراسة حالة. وتشير نتائج هذه الدراسة إلى أن فعالية برنامج STOPAN جزئية. انخفض عدد حالات الزواج من 6794 حالة (2021) إلى 3631 حالة (2024)، كما انخفضت نسبة النساء اللواتي تتراوح أعمارهن بين 20 و24 عامًا واللواتي تزوجن قبل سن 18 عامًا من 10.09% إلى 5.78%. ومع ذلك، لا تزال ممارسة الزواج غير المسجل شائعة في بعض المجتمعات. من منظور مقاصد الشريعة الإسلامية، يُسهم برنامج STOPAN في حماية الدين والحياة والعقل والذرية والممتلكات، على الرغم من أنه لم يصل إلى المستوى الأمثل بعد. توصي هذه الدراسة بتعزيز النهج المجتمعي ودمج القيم الدينية والثقافية المحلية في تنفيذ برنامج STOPAN. Abstrak Perkawinan anak di bawah umur masih menjadi persoalan sosial yang cukup krusial  di Indonesia, salah satu Provinsi dengan tingkat perkawinan di bawah umur tertinggi ada di Provinsi Jawa Barat secara nasional. Praktik ini tidak hanya melanggar hak anak, tetapi juga berdampak pada masa depan mereka, ada yang putus sekolah, kemiskinan berkelanjutan, dan kekerasan dalam rumah tangga. Untuk merespons persoalan ini, Pemerintah Provinsi Jawa Barat melalui Dinas Pemberdayaan Perempuan, Perlindungan Anak, dan Keluarga Berencana (DP3AKB) menginisiasi program Stop Perkawinan Anak (STOPAN). Program ini melibatkan kerja sama lintas sektor pemerintah, akademisi, dunia usaha, media, dan komunitas dengan pendekatan komprehensif dan partisipatif untuk menurunkan angka perkawinan anak. Penelitian ini bertujuan menganalisis implementasi program STOPAN dalam menurunkan angka perkawinan anak serta mengevaluasi efektivitasnya dari perspektif Maqashid Syariah. Pendekatan yang digunakan adalah kualitatif-deskriptif dengan metode studi kasus. Hasil penelitian ini menunjukkan bahwa STOPAN cukup efektif secara parsial. Jumlah dispensasi nikah menurun dari 6.794 kasus (2021) menjadi 3.631 kasus (2024), dan proporsi perempuan usia 20–24 tahun yang menikah sebelum 18 tahun juga menurun dari 10,09% menjadi 5,78%. Namun, praktik nikah siri masih kerap dilakukan beberapa masyarakat. Dalam perspektif Maqashid Syariah, STOPAN berkontribusi terhadap perlindungan agama, jiwa, akal, keturunan, dan harta, meskipun belum sepenuhnya optimal. Penelitian ini merekomendasikan penguatan pendekatan berbasis komunitas serta integrasi nilai keagamaan dan budaya lokal dalam pelaksanaan STOPAN.